Lymphocyte exhaustion in hepatocellular carcinoma: a dynamic evolution across disease stages - Fuster-Anglada, Carla; Corominas, Josep; Marsal, Aida; Llarch, Neus; Iserte, Gemma; Sanduzzi-Zamparelli, Marco; Forner, Alejandro; Ferrer-Fábrega, Joana; Holguin, Victor; Morales, Albert; Saavedra, Carolina; Reig, Maria; et al. (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have transformed cancer therapy. However, their efficacy in hepatocellular carcinoma (HCC) is limited, highlighting the need to further explore immune microenvironments and novel biomarkers. This study examined lymphocyte populations and immune checkpoint dynamics in early, advanced, and post-progression HCC to better understand immune dynamics in HCC and to help identify predictive biomarkers and immune modulation strategies.MethodsTumoral and non-tumoral liver tissues were analyzed from HCC patients across early (n=25), advanced (n=22), and advanced-beyond-progression (n=15) stages. Lymphocyte profiling was performed using immunohistochemistry and flow cytometry, focusing on NK cells, T cells, and immune exhaustion markers. An exploratory analysis of this profile and its association with disease progression and recurrence was conducted.ResultsEarly HCC exhibited higher liver-resident NK (lrNK) cell densities in non-tumor regions, which diminished with advanced stages. Increased CD56+ cell infiltration in the tumor core was associated with recurrence. Tumor region showed elevated PD-1, NKG2A, and CD39 expression in CD4+ and CD8+ T cells, indicating progressive immune exhaustion. Advanced HCC stages demonstrated altered NK cell phenotypes, with reduced cytotoxic activation (CD16) and increased residency markers (CXCR6/CD69) in tumor-isolated lymphocytes.ConclusionsProgressive immune exhaustion and dysregulation of lrNK and T cells in HCC reflect the evolution of the immune microenvironment originating in the tumor and leaking into the non-tumoral liver, progressively diminishing the cytotoxic capacity of NK and T cells. CD56+ cell density and immune checkpoint profiles are potential biomarkers for therapeutic response and disease monitoring, underscoring the need for personalized immunotherapy strategies.